Third-Party Market Cooperation and Non-Chinese Multinational Enterprises' Participation in the Belt and Road Initiative in Sub-Saharan Africa - Philipp von Carlowitz; Simon Züfle (Thunderbird International Business Review, 2025)
Non-Chinese multinational enterprises (MNE) are wondering whether China's Belt and Road Initiative (BRI) in Sub-Saharan Africa (SSA) creates challenges or opportunities for them. The fuzzy term “third-party market cooperation” was coined to involve non-Chinese MNEs in BRI-related business opportunities. Our contribution is threefold: First, we explore the role of non-Chinese firms in the BRI. Second, we locate “third-party market cooperation” in the international business literature and examine its originality. Third, we assess how non-Chinese MNEs can seize business potentials associated with third-party market cooperation in SSA. We conduct a qualitative analysis of official documents and substantiate our analysis by evaluating other media sources on third-party market cooperation projects in SSA. We find that firms play a decisive role in substantiating the BRI. The core novelty of third-party market cooperation is its strong political dimension, as governments may initiate and flank the participation of their MNEs in the BRI.
Keywords: 330; Africa; B2B; BRI; China; cooperation; international business; MNE; third-party market cooperation